Design of Fault Diagnosis System Based on Fuzzy Inference for a New Type Equipment. (June 2020) - Wang, Xin; Cui, He; Ji, Lu; Li, Yun
Abstract: Aimed at the puzzle of non-bijection between cause and symptom of the fault for a new type equipment system, the paper built the mathematical model of fuzzy inference by means of inference mecha- nism of fuzzy relation. In the paper, it designed the overall scheme of fault diagnosis system, and realized the function of system fault diagnosis by means of VC + + programming language according to the diagnosis flow of system. Through actual example validation, it shows that it satisfies the accuracy of fault diagnosis for a new type equipment system. The fault diagnosis of weapon equipment has always been an important topic for military research. With the change of war mode, higher requirements have been put forward for weapon equipment support technology. A new type of equipment is widely used in the land war, so some faults also appear one after another. In the long-term research, it is found that there is a fuzzy relationship between these fault phenomena and the causes. A fault does not correspond to a fault cause in modern mathematics, fuzzy mathematics can clarify the relationship between fault symptoms and fault causes in the equipment system. In this paper, the fuzzy fault diagnosis method is used to build a general fault diagnosis system to realize the fast and accurate analysis and diagnosis of faults.